Effect of a glyphosate formulation on freshwater plankton: A community combined metric approach - Polla, Wanda (2022)
Aim: The aim of this study was to experimentally assess the effects of glyphosate formulation on plankton composition by using different community parameters through a mesocosm experiment. Methodology: A 600 l mesocosm experiment was performed for 7 days, including a control (without glyphosate) and two concentrations of glyphosate. Results: Glyphosate caused a significant decrease in cladoceran density and a significant increase in rotifer, Chlorophyceae, and Euglenophyceae densities. In addition, zooplankton size diversity as well as microalgal evenness diminished. Interpretation:The decrease in cladoceran density may have benefited rotifers since they are less competitive for food resources. Moreover, the decrease in cladoceran foraging pressure over Chlorophyceae and Euglenophyceae may have benefited them. The different tolerances and competitiveness within the plankton components make the structure of this community a good indicator of environmental disturbance.